DOA and channel parameter estimation for wideband CDMA systems. - D'Amico, A.A (IEEE Transactions on wireless communications)
We consider the uplink of a direct-sequence code-division multiple-access system and we assume that the base station is endowed with a linear antenna array. Transmission takes place over a multipath channel and the goal is to estimate the channel parameters (path gains and delays) and the directions of arrival of the signal echoes from a user entering the network. We propose an estimator that operates in an iterative fashion and exploits knowledge of the transmitted symbols (training sequence). Compared to other existing schemes, it is simpler to implement as it reduces a complicated multidimensional optimization problem to a sequence of one-dimensional searches. Computer simulations indicate that the proposed scheme is useful even in applications over rapidly varying channels where the training sequence must be short compared with the channel decorrelation time.